2020
DOI: 10.3390/genes11111370
|View full text |Cite
|
Sign up to set email alerts
|

Plant Organellar DNA Polymerases Evolved Multifunctionality through the Acquisition of Novel Amino Acid Insertions

Abstract: The majority of DNA polymerases (DNAPs) are specialized enzymes with specific roles in DNA replication, translesion DNA synthesis (TLS), or DNA repair. The enzymatic characteristics to perform accurate DNA replication are in apparent contradiction with TLS or DNA repair abilities. For instance, replicative DNAPs incorporate nucleotides with high fidelity and processivity, whereas TLS DNAPs are low-fidelity polymerases with distributive nucleotide incorporation. Plant organelles (mitochondria and chloroplast) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 113 publications
(200 reference statements)
0
5
0
Order By: Relevance
“…Stably identified MTA for TGW under different treatments and combined BLUP, AX-94926681 located on chromosome 6A, was identified with transcript TraesCS6A02G402600. The locus codes for three major enzymes ribonuclease H-like and exonuclease and RNase T/DNA polymerase III were identified and are related to the enzymes responsible for nucleic acid metabolism, replication, homologous recombination, DNA repair, transposition ( Majorek et al., 2014 ), epigenetic changes at RNAPIII ( Hummel and Liu, 2022 ), and the repair of double-stranded breaks in Arabidopsis thaliana ( Peralta-Castro et al., 2020 ). Their presence as an integral part of the membrane and property of DNA binding further confirms the results based on gene ontology.…”
Section: Discussionmentioning
confidence: 99%
“…Stably identified MTA for TGW under different treatments and combined BLUP, AX-94926681 located on chromosome 6A, was identified with transcript TraesCS6A02G402600. The locus codes for three major enzymes ribonuclease H-like and exonuclease and RNase T/DNA polymerase III were identified and are related to the enzymes responsible for nucleic acid metabolism, replication, homologous recombination, DNA repair, transposition ( Majorek et al., 2014 ), epigenetic changes at RNAPIII ( Hummel and Liu, 2022 ), and the repair of double-stranded breaks in Arabidopsis thaliana ( Peralta-Castro et al., 2020 ). Their presence as an integral part of the membrane and property of DNA binding further confirms the results based on gene ontology.…”
Section: Discussionmentioning
confidence: 99%
“…However, despite the continuous assault of oxidative damage, sequence drift in both plant mitochondrial and chloroplast genomes remains very low, indicating the presence of an efficient organellar DNA damage repair system. Recently, several studies have demonstrated that as like nuclear genome, the BER pathway also participates in the repair of oxidative DNA damages in the organellar genome ( Boesch et al, 2009 ; Gredilla, 2010 ; Boesch et al, 2011 ; Prakash and Doublié, 2015 ; Peralta-Castro et al, 2020 ). BER in plants is a crucial genome defense pathway, comprising of sequential steps, including excision of the damaged DNA base, splitting of the sugar-phosphate backbone of DNA at the AP (apurinic/apyrimidinic) site, reorganizing the resulting DNA ends, filling of gaps through DNA replication and finally DNA strand ligation ( Roldán-Arjona et al, 2019 ).…”
Section: Dna Damage Repair Mechanisms In Plant Mitochondria and Chloroplastmentioning
confidence: 99%
“…In plants, mitochondria and chloroplast are double membrane bound semi autonomous organelles having self contained genetic materials (mt-DNA and cp-DNA, respectively) and equipped with the associated molecular machinery for regulation of gene expression ( Gutman and Niyogi, 2009 ; Smith and Keeling, 2015 ; Gray, 2017 ; Peralta-Castro et al, 2020 ). Both chloroplast and mitochondrial DNA have originated endosymbiotically from cyanobacteria and α-proteobacteria, respectively ( Sagan, 1967 ; Dyall et al, 2004 ; Chevigny et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…DNA molecules, however, are susceptible to damage of two types. Endogenous damage occurs when DNA polymerase makes mistakes [ 1 ], and when metabolic byproducts react with the DNA, either oxidatively or by glycation reactions [ 2 ]. Exogenous damage can be caused by radiation and toxins [ 3 ].…”
Section: Introductionmentioning
confidence: 99%